Compliance and Anti-Corruption Mechanisms in Industries in the South Region of Brazil - Deconto, Ana Claudia (2023)
The objective of this study was to identify the adherence of industrial companies to the criteria of the integrity program established in the anti-corruption law and the implementation of internal controls. Therefore, descriptive research was carried out, based on the application of a questionnaire, reaching a sample of 74 industries, 30% of which have been in operation for more than 41 years and 68% have family and/or mixed management. The results showed that the companies included in the sample have greater adherence to some criteria of the integrity program established by law, however, there are still opportunities for improvement in their control systems. When observing whether companies have a code of ethics, conduct and integrity, 51% have this document, 64% indicated that training on the subject takes place in the corporate environment and regarding the existence of an ethics committee or compliance and a whistleblower channel, the percentage of adherence can be considered relatively low, being 22% and 24%. When addressing the adoption of procedures and internal controls to avoid the occurrence of conflicts of interest and fraud, 50% of the companies have these procedures and 15% did not know how to respond. It was observed that Law 12.846/2013 is still little known, there is an awareness of its importance to reduce the risk of corruption, conflict of interest and increase the degree of transparency of actions, but at the same time, many entities do not yet have policies and procedures in place.